Gold Nanoparticles Modified With Polyethyleneimine Disturbed the Activity of Drug-Metabolic Enzymes and Induced Inflammation-Mediated Liver Injury in Mice - Chen, Hanqing; Zhou, Shuang; Zhu, Meilin; Wang, Bing; Chen, Wei; Zheng, Lingna; Wang, Meng; Feng, Weiyue (Frontiers in Pharmacology, 2021)
Gold nanoparticles (GNPs) have been used as a potential bioactive platform for drug delivery due to their unique optical and thermal characteristics. Liver is the main organ in orchestrating physiological homeostasis through metabolization of drugs and detoxification of exogenous substances. Therefore, it is crucial to deeply understand the mechanism of nanoparticle-liver interaction and the potential hepatic effects of GNPs in vivo. In this study, we studied the hepatic impacts of the intravenously injected polyethyleneimine (PEI)-modified GNPs (PEI-GNPs) on the expression of hepatic drug-metabolic enzymes and sterol responsive element binding protein 1c (SREBP-1c)-mediated de novo lipogenesis in mice for 24 h and 1 week. PEI-GNP accumulation in the liver is associated with increased liver inflammation, as evidenced by the gene expression of proinflammatory cytokines. Moreover, the GNP-induced hepatotoxicity in mice is partly due to liver inflammation-triggered disruption in the function of drug-metabolic enzymes, including hepatic uptake and efflux transporters, cytochrome P450 (CYP450), and UDP-glucuronosyltransferases (UGTs). The study provides evidence that it is necessary to consider the nanomaterial-liver interaction and manipulate the surface chemistry of GNPs prior to biomedical application of nanoparticles.